Autograft, allograft, and bone graft substitutes: clinical evidence and indications for use in the setting of orthopaedic trauma surgery - Baldwin, Paul; Li, Deborah J; Auston, Darryl A; Mir, Hassan S; Yoon, Richard S; Koval, Kenneth J (Journal of orthopaedic trauma, 2019)
Bone grafts are the second most common tissue transplanted in the United States, and they are an essential treatment tool in the field of acute and reconstructive traumatic orthopaedic surgery. Available in cancellous, cortical, or bone marrow aspirate form, autogenous bone graft is regarded as the gold standard in the treatment of post-traumatic conditions such as fracture, delayed union, and nonunion. However, drawbacks including donor-site morbidity and limited quantity of graft available for harvest makes autograft a less-than-ideal option for certain patient populations. Advancements in allograft and bone graft substitutes in the past decade have created viable alternatives that circumvent some of the weak points of autografts. Allograft is a favorable alternative for its convenience, abundance, and lack of procurement-related patient morbidity. Options include structural, particulate, and demineralized bone matrix form. Commonly used bone graft substitutes include calcium phosphate and calcium sulfate synthetics -these grafts provide their own benefits in structural support and availability. Additionally, different growth factors including bone morphogenic proteins can augment the healing process of bony defects treated with grafts. Autograft, allograft, and bone graft substitutes all possess their own varying degrees of osteogenic, osteoconductive, and osteoinductive properties that make them better suited for different procedures. It is the purpose of this review to characterize these properties and present clinical evidence supporting their indications for use in the hopes of better elucidating treatment options for patients requiring bone grafting in an orthopaedic trauma setting.